(untitled) (Research, Society and Development, 2024)
Objective: The study aimed to understand the role of nurses in aesthetics in a municipality in the Southwest of Paraná State, Brazil. Methodology: Social, descriptive, field, cross-sectional, and qualitative research was carried out, which collected data through open interviews and used Bardin’s method to describe them. Results: The sample consisted of eight professionals working around aesthetics, who developed various procedures, especially injectable ones, such as collagen biostimulators, botulinum toxin, and fillers. The participating nurses reported professional recognition and satisfaction, remuneration, flexible working hours, autonomy, and shorter working hours, as benefits of this work. On the other hand, they highlighted the acquisition of materials and difficulties at the beginning of the work process as difficulties faced. Conclusion: The work of nurses in the aesthetic area enables intellectual and financial growth, as well as personal and professional satisfaction. It is a growing field of activity, that involves technical capacity, skill, and nurse competence.